1994
DOI: 10.1073/pnas.91.11.4897
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-derived second messenger regulates x-ray-mediated tumor necrosis factor alpha gene induction.

Abstract: Cells adapt to adverse environmental conditions through a wide range of responses that are conserved throughout evolution. Physical agents such as Ionizing radiation are known to initiate a stress response that is triggered by the recognition of DNA damage. We have identified a sgnlIng pathway involving the activation of phospholipase A2 and protein kinase C in human cells that confers x-ray induction of the tumor necrosis factor a gene. Treatment of human cells with ionizing radiation or H202 was associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 55 publications
(72 reference statements)
1
13
0
Order By: Relevance
“…For example, exposure of epithelial cells to 100-200 cGy irradiation has been demonstrated to induce egr-1, NF-␤, c-jun, c-fos and other transcriptional stimulatory elements. [6][7][8][9][10][11][12][13] These transcriptional regulators activate genes for many cytokine regulators and cellular protective gene products. 9,28 Radioresistance of mammalian cells in culture can be induced by the expression of recombinant oncogenes of several categories 47 or by increasing the availability of specific recombinant growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, exposure of epithelial cells to 100-200 cGy irradiation has been demonstrated to induce egr-1, NF-␤, c-jun, c-fos and other transcriptional stimulatory elements. [6][7][8][9][10][11][12][13] These transcriptional regulators activate genes for many cytokine regulators and cellular protective gene products. 9,28 Radioresistance of mammalian cells in culture can be induced by the expression of recombinant oncogenes of several categories 47 or by increasing the availability of specific recombinant growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…Several well documented biochemical and molecular mechanisms are known to cause a corticosteroid induced enhancement of cellular resistance to cytotoxic treatment, namely, a dexamethasone induced increase in cellular glutathione content [15], a dexamethasone induced enhancement in expression of the metallothionein gene [19], and a dexamethasoneinducible suppression of radiation induced secretion of tumor necrosis factor alpha (TNFa), a protein enhancing cell inactivation by ionizing radiation [5][6][7]. In addition, we have found some preliminary evidence indicating that there may be a direct activation of DNA repair mechanisms and an inhibition of apoptotic responses following DNA damage (unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…However, PKC-s has been shown to be induced by ionizing radiation (36) and recent experiments indicate that PKC-e is much less abundant in AT cell lines (37). Hallahan et al (38) have demonstrated that the ionizing radiation-induced signal required for transcriptional induction of the tumor necrosis factor a gene involves the activation of phospholipase A2 at the cell membrane and, subsequently, PKC activity. Interestingly, overexpression of phospholipase A2 has also been shown to complement partially the ionizing radiation sensitivity of AT group D cell lines §.…”
Section: Resultsmentioning
confidence: 99%